Time bomb eaudiobook - Charbonneau, Joelle (Recorded Books Inc., 2018)
Seven students trapped in their school after a bomb goes off must fight to survive while also discovering who among them is the bomber in this provocative new thriller from the author of the New York Times bestselling Testing Trilogy. Perfect for fans of This Is Where It Ends. A congressman's daughter who has to be perfect. A star quarterback with a secret. A guy who's tired of being ignored. A clarinet player who's done trying to fit in. An orphaned rebel who wants to teach someone a lesson. A guy who wants people to see him, not his religion. They couldn't be more different, but before the morning's over, they'll all be trapped in a school that's been rocked by a bombing. When they hear that someone inside is the bomber, they'll also be looking to one another for answers. Told from multiple perspectives, Time Bomb will keep readers guessing about who the bomber could be-and what motivated such drastic action.